The Impact of Digital Marketing on E-commerce Development of Fashion Retailer Groups : The case of Dior, Prada and LVMH - Nefodova, Anna (2021)
This bachelor thesis attempts to examine the weak and strong aspects of digital marketing tools with the focus on social media platforms for improving the ecommerce efficiency of Dior, Prada and Louis Vuitton. The methods preferred were the use of both qualitative and quantitive methods for structuring this study. In order to gather necessary data on construction of the theoretical part, the author provides the secondary literature on specific forms of ecommerce and its development, profiles of the major companies, and analysis of data on their profit trends and marketing strategies. First the increasing importance of e commerce for modern industries is delineated and special relevance for the fashion industry is established. Next, the relationship of eco mmerce and digital marketing, with focus on Facebook and Instagram, search engine optimization and mobile media such as apps, is discussed. Finally, to collect the primary data, there was used empirical approach each company is profiled, and an analysis of the brands’ major marketing strategies and revenue is provided. Results suggest a primary place of importance for online search traffic. Organic search terms are shown to drive more traffic revenue than company sponsored paid keywords. Trends for nationa l markets are less pronounced. The contribution from specific social media networks is also assessed and the leading contributors are identified. Some potential suggestions for the brands are made on the basis of their profiles and trends. The thesis sugge that digital marketing is a growing component of ests commerce that companies should invest in and take into account.